THE OLIGOCENE–MIOCENE MENILITE FORMATION IN THE UKRAINIAN CARPATHIANS: A WORLD‐CLASS SOURCE ROCK. (16th September 2019) - Rauball, J. F.; Sachsenhofer, R. F.; Bechtel, A.; Coric, S.; Gratzer, R.
Abstract : This study investigates the hydrocarbon potential of Oligocene–Miocene shales in the Menilite Formation, the main source rock in the Ukrainian Carpathians. The study is based on the analysis of 233 samples collected from outcrops along the Chechva River in western Ukraine in order to analyse bulk parameters (TOC, Rock‐Eval), biomarkers and maceral composition. In Ukraine, the Menilite Formation is conventionally divided into Lower (Lower Oligocene), Middle (Upper Oligocene) and Upper (Lower Miocene) Members. The Early Oligocene and Early Miocene ages of the lower and upper members are confirmed by new nannoplankton data. The Lower Menilite Member is approximately 330 m thick in the study area and contains numerous chert beds and turbidite sandstones in its lower part together with organic‐rich black shales. The shales have a high content of silica which was probably derived from siliceous micro‐organisms. The TOC content of the shales frequently exceeds 20 wt.% and averages 9.76 wt.%. HI values range between 600 and 300 mgHC/gTOC (max. 800 mgHC/gTOC). The Middle Member contains thin black shale intervals but was not studied in detail. The Upper Member is about 1300 m thick in the study area and is composed mainly of organic‐rich shales. Chert layers are present near the base of the Member, and a prominent tuff horizon in the upper part represents a volcanic phase during shale deposition. The member grades into overlying molasse sediments. The average TOC content of the Upper Menilite succession is 5.17 wt.% but exceeds 20 wt.% near its base. Low Tmax and vitrinite reflectance measurements for the Lower (419°C and 0.24–0.34 %Rr, respectively) and Upper (425°C and 0.26–0.32 %Rr, respectively) Menilite Member successions indicate thermal immaturity. Biomarker and maceral data suggest a dominantly marine (Type II) organic matter input mixed with varying amounts of land‐plant derived material, and indicate varying redox and salinity conditions during deposition. Determination of the Source Potential Index (SPI) shows that the Menilite Formation in the study area has the potential to generate up to 74.5 tons of hydrocarbons per m 2 . The Chechva River outcrops therefore appear to have a significantly higher generation potential than other source rocks in the Paratethys realm. These very high SPI values for the Menilite Formation may explain why a relatively small area in Ukraine hosts about 70% of the known hydrocarbon reserves in the northern and eastern Carpathian fold‐thrust belt.